Insect galls associated with Copaifera sabulicola J.A.S Costa & L.P Queiroz (Fabaceae): Characterization and new records - Edyany Kellen Souza Soares; Andréia Barroncas de Oliveira; Valdeir Pereira Lima; Daniéla Calado (Revista Brasileira de Entomologia, 2022)
ABSTRACT Among the plant diversity of the Cerrado, the genus Copaifera is commonly associated with galling insects. Here, we expand the knowledge about insect galls on Copaifera sabulicola J.A.S Costa & L.P. Queiroz (Fabaceae) by characterizing their occurrence in a stricto sensu vegetation area of the Brazilian Cerrado, Western Bahia, Brazil throughout the year. We randomly sampled 60 branches (50 cm long) from individuals of C. sabulicola, from April 2015 to March 2016. We found 11 morphotypes for C. sabulicola, of which 5 are new records. Further, we identified six gall-inducing insects, all belonging to Cecidomyiidae family. Regarding other arthropods associated with C. sabulicola, we observed inquilines, successors, and parasitoids, belonging to the orders Collembola, Hemiptera, Hymenoptera and Acari. The parasitoid fauna included three families of the order Hymenoptera: Braconidae, Encyrtidae and Eulophidae.